Inferred oviraptorosaur footprints in the Apenninic Carbonate Platform: New tools for the identification of trackmakers from the Sezze ichnosite (lower-middle Cenomanian; central Italy). (January 2023) - Antonelli, Matteo; Romano, Marco; De Sario, Federico; Pignatti, Johannes; Sacco, Enrico; Petti, Fabio Massimo
Abstract: Herein we apply a new approach to the study of theropod footprints with elongated metatarsal traces from the Upper Cretaceous (lower-middle Cenomanian) Sezze ichnosite (Latium, central Italy). In this study, we combine traditional methods and new tools (i.e., close-range digital photogrammetry, sUAS – small Unmanned Aerial System, Principal Component Analysis, and Cluster Analysis) to identify the osteological features of the foot mirrored in the traces, analyse the differential depth of impressions and reconstruct the anatomical structure of the trackmaker foot. The use of close-range photogrammetry allows us to improve the ichnological interpretation and analysis, focusing on anatomical features such as phalangeal pads and claw traces. A dataset consisting of measurements of 66 foot skeletons of theropods and the five best preserved elongated footprints with metatarsal trace was subjected to Principal Component Analysis and Cluster Analysis, to investigate the morphospace occupied by the principal clade of theropods and find the most likely trackmaker among known taxa. The results indicate the clade of Oviraptorosauria as the more consistent producers for the Sezze theropod footprints, opening new questions about the clade dispersal and on the complex paleobiogeography of the Appenninic Carbonate Platform in the Late Cretaceous. The integrated multidisciplinary approach (high-resolution photogrammetry and morphometric analysis) confirms the utility of the new technological methodologies for the ichnological study.